PECULIARITIES OF TEACHING SYNONYMOUS SERIES TO JUNIOR SCHOOL CHILDREN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
Teaching synonymous series to junior school children presents a unique set of challenges and opportunities. This paper explores the peculiarities of this pedagogical endeavor, focusing on the significance of vocabulary development, cognitive development, age-appropriate teaching methods, and the role of contextual understanding. By understanding these peculiarities, educators can design effective strategies to enhance students' lexical and cognitive abilities, thereby preparing them for more advanced language skills in the future.